Information asymmetries between parents and educators in German childcare institutions - Georg F. Camehl; Pia S. Schober; C. Katharina Spiess (Education Economics, 2018)
Economic theory predicts market failure in the market for early childhood education and care (ECEC) due to information asymmetries. We empirically investigate information asymmetries between parents and ECEC professionals in Germany, making use of a unique extension of the Socio-Economic Panel Study (SOEP). We compare quality perceptions by parents and by professionals across 734 institutions. We detect considerable information asymmetries that differ across quality measures but less so by parental socio-economic background or center characteristics. Both similarly contribute to explaining variations in the information gap. We conclude that information is not readily available to parents; an issue that should be addressed by policy-makers.
Keywords: J13; D83; I21; 300; childcare; quality; information asymmetries; socio-economic differences